Testosterone Biosynthesis from 4-Androstene-3,17-Dione Catalyzed via Bifunctional Ketoreductase - Yi Wei; Guangyao Mei; Jinlin Zhao; Shaoyang Zhang; Wenping Qin; Qing Sheng; Zhongyi Yang (Fermentation, 2023)
Testosterone (TS) is an important androgen drug and a precursor of steroid drug synthesis. Ketoreductase 2 (KR-2) (GenBank accession no. ABP64403.1) is observed to stereo-selectively catalyze the bioreduction of 4-androstene-3,17-dione (4-AD) to testosterone and contribute to the regeneration of NADH using isopropanol as a co-substrate. The Km value of KR-2 was 2.22 mmol/L with 4-AD, and the optimal pH was 6.5–7.0. The enzyme is stable and demonstrates relatively high-level enzyme activity at 40 °C. Acetone significantly inhibits this activity. This inhibition was overcome using an intermittent vacuum during the reaction process. Finally, the amount of TS reached 65.42 g/L after a 52 h reaction with 65.8 g/L 4-AD, 10% isopropanol, and 2 g/L β–NAD+ at 40 °C, with a conversion rate of 98.73%. A total of 6.15 g of TS was obtained from 6.58 g of 4-AD after the reaction and purification; the HPLC purity was 99.82%, and the overall yield was 92.81%. This enzyme provides a promising route for the green biosynthesis of testosterone for industrial applications.